2007
DOI: 10.1128/aem.00956-07
|View full text |Cite
|
Sign up to set email alerts
|

Reconstitution of Glyphosate Resistance from a Split 5-Enolpyruvyl Shikimate-3-Phosphate Synthase Gene in Escherichia coli and Transgenic Tobacco

Abstract: A highly N-phosphonomethylglycine (glyphosate)-resistant Pseudomonas fluorescens G2 5-enolpyruvyl shikimate-3-phosphate synthase (EPSPS) was mapped to identify potential split sites using a transposon-based linker-scanning procedure. Intein-mediated protein complementation was used to reconstitute glyphosate resistance from the genetically divided G2 EPSPS gene in Escherichia coli strain ER2799 and transgenic tobacco.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 27 publications
3
20
0
Order By: Relevance
“…In good agreement with results from other works, which showed that seeds were usually inhibited under glyphosate stress (Dun et al 2007), we observed that approximately 85 % of the seeds of VvEPSPS mutanttransgenic plants germinated well in 1000 lM glyphosate, whereas approximately 30 % seeds of CK and VvEPSPS-transgenic plants germinated at 200 lM glyphosate, although germination was completely inhibited at 1000 lM glyphosate (Fig. 3a).…”
Section: Assay For the Glyphosate Resistance Of Transgenic Arabidopsissupporting
confidence: 94%
“…In good agreement with results from other works, which showed that seeds were usually inhibited under glyphosate stress (Dun et al 2007), we observed that approximately 85 % of the seeds of VvEPSPS mutanttransgenic plants germinated well in 1000 lM glyphosate, whereas approximately 30 % seeds of CK and VvEPSPS-transgenic plants germinated at 200 lM glyphosate, although germination was completely inhibited at 1000 lM glyphosate (Fig. 3a).…”
Section: Assay For the Glyphosate Resistance Of Transgenic Arabidopsissupporting
confidence: 94%
“…Glyphosate can affect seed germination. Seeds are usually poorly developed under glyphosate stress (7). Figure 4 shows that AroA mutant -transgenic plants grew well in 750 M glyphosate, whereas AroA O.anthropi -transgenic plants did not grow at 500 M. The control plants grew only at 250 M.…”
Section: Resultsmentioning
confidence: 99%
“…For example, the metabolic enzyme acetolactate synthase has been split and successfully reconstituted by PTS in E. coli (80). In a similar fashion, the bacterial 5-enolpyruvylshikimate-3-phosphate synthase (EPSPS) was also reconstituted by PTS in the chloroplasts of Nicotiana tabacum to produce an herbicide-resistant transgenic crop (81,82). By splitting the gene between nuclear and chloroplast chromosomes, the potential for recombination and transfer to an undesired host is strongly inhibited.…”
Section: Gene Delivery and Control In Transgenic Organismsmentioning
confidence: 99%